Long Non-coding RNAs Contribute to the Inhibition of Proliferation and EMT by Pterostilbene in Human Breast Cancer - Huang, Yongye; Du, Juan; Mi, Yan; Li, Tianye; Gong, Ying; Ouyang, Hongsheng; Hou, Yue (Frontiers in Oncology, 2018)
Background: There is increasing evidence that long noncoding RNAs (lncRNAs) are involved in the process of carcinogenesis and treatment using chemotherapy. Pterostilbene, a phytochemical agent with natural antioxidant and anti-inflammatory properties, has been shown to modulate oncogenic processes in many cancers. However, there has been only limited study of the association between pterostilbene and expression of lncRNAs. Methods: MCF7 breast cancer cells were treated with various concentration of peterstilbene; and their gene expression profile analyzed by quantitative real-time PCR, Western blotting and immunofluorescence. Results: Treatment with pterostilbene inhibited cell proliferation and epithelial-to-mesenchymal transition (EMT), and increased cell apoptosis, autophagy and ER stress. The Akt/mTOR pathway was down-regulated, but p38 MAPK/Erk signaling was activated in cells following treatment with pterostilbene. Pterostilbene increased the expression of the lncRNAs MEG3, TUG1, H19 and DICER1-AS1 whereas the expression of LINC01121, PTTG3P and HOTAIR declined. Knockdown of lncRNA H19 resulted in a reduction of the cell invasion, the cells becoming more sensitive to pterostilbene therapy. Conclusions: These results suggest that efficient optimum disruption of lncRNA expression might possibly improve the anti-tumor effects of phytochemical agents, thus serving as a potential therapy for breast cancer.